Recent update on discovery and development of Hsp90 inhibitors as senolytic agents - Gupta, Sayan Dutta; Pan, Cheol Ho (ELSEVIER, 2020)
Hsp90 chaperone is an encouraging target for the development of novel anticancer agents. The failure of Hsp90 inhibitors to get regulatory approval for the treatment of cancer is hindered due to toxicity, cost involved in their development and formulation issues. The inhibitors against this chaperone are also being evaluated in pre-clinical models for the treatment of diseases other than cancer (Alzheimer, malaria, AIDS, etc.). Recently, Hsp90 inhibitors have shown promising senolytic effect that is helpful in increasing the health and life span of mice. The senolytic property of Hsp90 inhibitors will make them less toxic for use in humans. The review focuses on Hsp90 inhibitors discovered till date as senolytic agents along with their future prospects. Further, the various models used for the evaluation of senolytic effect are also discussed. (c) 2020 Elsevier B.V. All rights reserved.
Keywords: PROTEIN 90 INHIBITOR; MOLECULAR CHAPERONE HSP90; TRANSCRIPTION FACTOR HSF1; ARF TUMOR-SUPPRESSOR; PHASE-II TRIAL; ANTITUMOR-ACTIVITY; IN-VITRO; PROTEASOMAL DEGRADATION; CELLULAR SENESCENCE; CRYSTAL-STRUCTURE